2021
DOI: 10.1016/j.tcm.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Update on acute myocarditis

Abstract: Acute myocarditis (AM), a recent-onset inflammation of the heart, has heterogeneous clinical presentations, varying from minor symptoms to high-risk cardiac conditions with severe heart failure, refractory arrhythmias, and cardiogenic shock. AM is moving from being a definitive diagnosis based on histological evidence of inflammatory infiltrates on cardiac tissue to a working diagnosis supported by high sensitivity troponin increase in association with specific cardiac magnetic resonance imaging (CMRI) finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 88 publications
(89 reference statements)
4
87
0
12
Order By: Relevance
“…146 Our therapeutic approach is supported by Ammirati's work by placing an emphasis on the importance of both MCS and immunomodulation therapy. 45,147 We propose this is the key to a successful treatment of FM. However, there are some differences between the two regimens.…”
Section: Prognosis Of Fmmentioning
confidence: 99%
“…146 Our therapeutic approach is supported by Ammirati's work by placing an emphasis on the importance of both MCS and immunomodulation therapy. 45,147 We propose this is the key to a successful treatment of FM. However, there are some differences between the two regimens.…”
Section: Prognosis Of Fmmentioning
confidence: 99%
“…ICI-related myocarditis differs from classical acute myocarditis (which is generally caused by a post-viral immune response) in terms of both clinical presentations and outcomes [ 3 , 4 ]. Patients with ICI-related myocarditis are typically older than patients with non-ICI-related forms of myocarditis (64 years versus 34 years), have other chronic comorbidities in addition to their cancer, and show a higher mortality rate [ 5 ]. Identification of clinical risk factors predicting ICI-related myocarditis therefore is of primary importance, especially in view of increased ICI prescription [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infection with the novel pathogen severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may trigger myocarditis both directly and indirectly ( 14 , 21 ). Several studies have suggested that the immune response triggered by the virus is the major cause of cardiomyocyte injury, rather than direct virus-mediated cytotoxicity ( 15 , 22 ). In a recent series of hospitalized coronavirus disease 2019 (COVID-19) cases caused by SARS-CoV-2 infection, acute cardiac injury with serum troponin elevation occurred in 7% to 27% of patients, and elevated troponin levels were associated with increased mortality in patients with COVID-19 ( 23 25 ).…”
Section: Triggers Of Myocarditismentioning
confidence: 99%